Advances in fresh-cut fruits and vegetables processing - Martin-Belloso, Olga.; Soliva-Fortuny, Robert (Boca Raton, FL : CRC Press, 2011)
'Taking a multidisciplinary approach, this work explores the basics and the more recent innovations in fresh-cut fruit and vegetable processing. It addresses scientific progress in the fresh-cut area and discusses the industry and the market for these commodities. In addition, the book covers the regulations that affect the quality of the final products and their processing as well as consumers' attitude and sensory perceptions. The design of plants and equipment is also presented, taking into account engineering aspects, safety, and HACCP guidelines. Finally, innovations with regard to healthy and attractive products are examined'--
Includes bibliographical references and index.
Keywords: Fruit -- Processing; Vegetables -- Processing; Fruit -- Preservation; Vegetables -- Preservation; Food contamination -- Prevention